Evaluating Evaluating Program ESCO Saturday Thought Used CIPP Model : Evaluating Program ESCO Saturday Thought Used CIPP Model (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to evaluate the ESCO Saturday program at the English Student Community (ESCO) of UIN Fatmawati Sukarno Bengkulu by using the CIPP evaluation model (Context, Input, Process, and Product). The study employed a qualitative descriptive method with data collected through interviews, observations, and questionnaires involving ESCO administrators, tutors, and members.The results of the Context evaluation revealed that the program was relevant to students’ needs for improving English skills, but lacked a clear organizational foundation and legal framework such as AD/ART. The Input evaluation indicated limited human resources, inadequate facilities, and the absence of systematic training for tutors. The Process evaluation showed that the program implementation tended to be sporadic, poorly documented, and lacked structured planning or evaluation. Meanwhile, the Product evaluation demonstrated that although the program contributed to students’ English competence and confidence, it had not yet achieved the expected outcomes due to inconsistent follow-up and limited sustainability.Overall, the study concludes that ESCO Saturday needs significant improvement in organizational management, human resource development, and program planning. It is recommended to establish a strong organizational structure, conduct a comprehensive needs analysis, and design sustainable programs aligned with ESCO’s vision and mission to ensure long-term effectiveness and impact.